PEMBERDAYAAN PENGAWAS SEKOLAH DALAM UPAYA MENINGKATKAN KINERJA KEPALA SEKOLAH MENENGAH ATAS NEGERI DI KOTA SINGKAWANG - A l k a d r i A l k a d r i (Jurnal Manajemen Pendidikan, 2010)
The empowerment of supervisors in this reserach is giving the powerful/authority to the school supervisor to do their duty and responsibilities to achieve the purpose. empowerment of supervisors activities are planning, controlling, supervising, evaluating, guiding and developing, reporting and follow up. The objective of this research is to get the whole description about the empowerment of supervisors to increase the principal performance. The results of this research indicated that the empowerment of supervisors have been done well in Singkawang. Most of the school supervisor have been given powerful and authority that suitable with their duty and function; besides they have given education, training, seminar, joined in meeting and workshop. However, the improvement of qualification, competence and supervisor sertification which is needed in the future that suitable with the minister regulation of national education (Permendiknas Nomor 12 Tahun 2007). As well as the principal performance have been done well. The principal have done their duty and responsibilities as educator, manager, administrator, supervisor, leader, inovator, and motivator. The improvement of qualification, competence and sertification head master which is needed in the future that suitable with the minister regulation of national education (Permendiknas Nomor 13 Tahun 2007). The conclusion of this research that; The empowerment of supervisors and principal performance have gone well in Singkawang city. Nevertheless, in the future must done the increase of qualification, competence and sertification especially for school supervison and principal position.